Health care issues in rural areas - Stimers, Mitchel James (Applied Geography Conferences, 2007)
The availability of healthcare in rural regions is an important area of study, since healthcare is a need of all people, but rural residents often lack access to quality care. This paper reviews current literature concerning issues related to healthcare in rural areas, with an emphasis on rural-urban differences and consideration in providing appropriate services to residents of rural areas. Topics examined include types of trauma that are more prevalent in rural areas, and how emergency service personnel handle those types of trauma. Proper first-response care and transportation of trauma victims is extremely important to their chances of survival. Literature concerning the quality of emergency service personnel, transport issues such as response time and instances of inappropriate transport, and the quality and availability of trained personnel at the receiving hospital will be reviewed. Specific conditions such as heart attacks and strokes will also be examined.
Keywords: Rural healthcare; Rural geography; Healthcare review